The Role of Capital Ratios in Predicting Bank Distress: Evidence from the Nigerian Banks - Aliero, Haruna Mohammed; Gatawa, Nasiru Mukhtar; Kabiru, Alhaji (Advances in Social Sciences Research Journal, 2016)
The study examines the relationship between capital ratios and bank distress in so doing the efficiency of different capital ratios (risk weighted, and non-risk weighted) have been compared in predicting bank distress. Secondary data was collected from the Central Bank of Nigeria statistical bulletin for fifteen years (1995-2000). The data was analyzed through the use of Ordinary Least Squares method (OLS), Granger causality test and T-Test respectively. The results from the study show that the two capital ratios (risk-weighted and liquidity ratios) predict distress significantly while the other ratio (equity ratio) proved to be ineffective in predicting bank distress. The result also shows significant difference in the level of efficiency of the three capital ratios in distress prediction. Therefore, the continued use of risk weighted ratio in the prediction of bank distress is suggested, while liquidity ratio is recommended to supplement it. However, liquidity ratio and equity ratio should not be used to replace risk weighted capital ratio as each one of them has its unique importance.